Impact of preoperative patient education on the prevention of postoperative complications after major visceral surgery: the cluster randomized controlled PEDUCAT trial - Klaiber, Ulla; Stephan-Paulsen, Lisa M.; Bruckner, Thomas; Müller, Gisela; Auer, Silke; Farrenkopf, Ingrid; Müller-Christmann, Christine; Dörr-Harim, Colette; Diener, Markus K.; Büchler, Markus W.; Knebel, Phillip (Trials, 2018)
The prevention of postoperative complications is of prime importance after complex elective abdominal operations. Preoperative patient education may prevent postoperative complications and improve patients’ wellbeing, but evidence for its efficacy is poor. The aims of the PEDUCAT trial were (a) to assess the impact of preoperative patient education on postoperative complications and patient-reported outcomes in patients scheduled for elective complex visceral surgery and (b) to evaluate the feasibility of cluster randomization in this setting.